Growth Behavior and Productivity of Intercrops under Gmelina arborea Based Agroforestry Systems - , Rajendra Prasad Dongre; , R. Bajpai; , Vishnu Solanki; , S.B. Das; , Yashpal Singh; , Ajay Kumar Shah; , Kailash Kumar; , Pavan Chouksey (Archives of Current Research International, 2025)
Agroforestry and intercropping systems offer sustainable alternatives to monoculture, enhancing yield stability and ecosystem services. This study investigated the growth behavior and productivity of three intercrops – Cajanus cajan (Arhar), Vigna unguiculata (Cowpea), and Brassica juncea (Mustard) – within a Gmelina arborea-based agroforestry system compared to their sole cropping counterparts. The field experiment was conducted over two consecutive years (2019-20 and 2020-21) at the Forestry Research Farm, JNKVV, Jabalpur, using a Complete Randomized Block Design with seven treatments (three intercropping combinations, sole Gmelina, and three sole crops) replicated three times. Data were collected on plant population, height, branches per plant, pods/siliques per plant, grains per pod/silique, and grain, straw, and biological yields. Results indicated that sole cropping treatments generally maintained higher plant populations per meter row compared to intercropping under Gmelina. However, growth parameters varied significantly; Gmelina with Arhar (T1) consistently recorded the highest crop height, branches per plant, and total pods per plant across both years and in pooled data, significantly outperforming most other treatments in pod production. Gmelina with Mustard (T3) exhibited high potential, particularly in grain and biological yield, especially in the first year. While sole Arhar (T5) also performed well, particularly for yield components, intercropping combinations demonstrated viable productivity. A general decline in intercrop performance was observed in the second year when Gmelina trees were older. The findings suggest that Gmelina-based agroforestry systems can support diverse crop production, with specific combinations like Gmelina-Arhar and Gmelina-Mustard showing promise, although tree presence influences crop density and yield dynamics over time.